Estimação de canal no enlace reverso de sistemas VL-MIMO multi-celulares - Osterno, Igor Sousa (2015)
The aim of this dissertation is mainly to investigate and propose different channel estimation techniques for a multicell multiuser multiple-input multiple-output (MIMO) communication system. Particular attention is payed to the case that is referred to as very large (VL) MIMO (VL-MIMO) arrays, where the base stations are equipped with a great (or even huge) number of antenna sensors. Some of these techniques exploit properties issued from the (large) Random Matrices Theory and are therefore less affected by the so-called pilot contamination effect. In this work, the parameters of the VL-MIMO channel are estimated from the eigenvalue decomposition (EVD) of the output covariance matrix of the receive antenna array. This technique is more robust to the interference of signals from other cells compared with methods that do not exploit the specific properties of the VL-MIMO channel matrix, which is the case of the classical least squares (LS) solution. In this context, this work also proposes a simpler way to resolve the scaling ambiguity remaining from the EVD-based method using the Khatri-Rao product. The second part of this dissertation exploits the VL-MIMO properties on a source localization problem, aiming to determine the direction of arrival (DoA) of the signals impinging on the antenna array from a given desired cell. Based on the subspace representation of the outer cell interference signals, we propose a new blind MUSIC-like classification algorithm to estimate the channel matrix. The proposed technique convert the high resolution gains of the VL-MIMO arrays into ability to reduce power of undesired signals, yielding good channel estimates even under high interference power levels, and including cases where desired and undesired signals are strongly correlated. Computer simulations have been done in order to cope with different situations and propagation scenarios, thus yielding an exploratory character to our research and allowing us to evaluate and assess the investigated algorithms, comparing them to consolidated solutions in order to establish a complete overview of the parameter estimation problem in the VL-MIMO case